Learning Assistance Services in Development Early Children in Play Group - Hafidz, Nur; Prima, Ellen (Indonesian Journal of Early Childhood Education Studies, 2020)
Tutoring services are a form of assistance provided to individuals to overcome problems in learning activities so that after going through the change process in learning they can achieve optimal learning outcomes. Tutoring for students is more focused on improving learning achievement and aspects of child development. The learning achievement and development of this child are programmed by the Play Group and the Early Childhood Education unit. The program is implemented to support the guidance of early detection learning services for growth and development, the formation of Islamic habit, art classes, and reading aloud. The research objective was to see the tutoring process in child development in the Wadas Kelir South Purwokerto Study Group. Therefore, the implementation of tutoring that has positive learning attitudes and habits, such as reading books, learning the discipline of many things, having attention to all lessons, and actively participating in all learning activities programmed in KB Wadas Kelir, South Purwokerto. The research used a qualitative descriptive research method. The research subjects included the principal, class teachers (stars, moon, sun), parents, and children of KB Wadas Kelir South Purwokerto. The object of research is the role of tutoring services in child development at KB Wadas Kelir South Purwokerto. The data method used is observation, interview, documentation. The technical analysis used is data reduction, data presentation, and conclusion. The results describe learning services in the aspects of child development carried out in the Wadas Kelir South Purwokerto Learning Group, Banyumas Regency.